Heterogeneous catalysis for energy applications - Reina, Tomas R.; Odriozola, Jose A. (Royal Society of Chemistry, 2020)
Heterogeneous catalysis plays a central role in the global energy paradigm, with practically all energy-related process relying on a catalyst at a certain point. The application of heterogeneous catalysts will be of paramount importance to achieve the transition towards low carbon and sustainable societies. This book provides an overview of the design, limitations and challenges of heterogeneous catalysts for energy applications. In an attempt to cover a broad spectrum of scenarios, the book considers traditional processes linked to fossil fuels such as reforming and hydrocracking, as well as catalysis for sustainable energy applications such as hydrogen production, photocatalysis, biomass upgrading and conversion of CO2 to clean fuels. Novel approaches in catalysts design are covered, including microchannel reactors and structured catalysts, catalytic membranes and ionic liquids. With contributions from leaders in the field, Heterogeneous Catalysis for Energy Applications will be an essential toolkit for chemists, physicists, chemical engineers and industrials working on energy.
Keywords: Heterogeneous catalysis.; Power resources.; elektronické knihy; electronic books